1986
DOI: 10.1002/hep.1840060519
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of preoperatively obtained clinical and laboratory data in predicting survival following orthotopic liver transplantation

Abstract: Twenty-seven clinical and laboratory data and the subsequent clinical course of 93 consecutive adult patients who underwent orthotopic liver transplantation for various chronic advanced liver diseases were analyzed retrospectively to assess the risk factors of early major bacterial infection and death after the procedure. Forty-one patients (44%) had early major bacterial infection during hospitalization for orthotopic liver transplantation. The mortality rate was 70.7% in patients with early major bacterial i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
60
2

Year Published

1987
1987
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(63 citation statements)
references
References 14 publications
1
60
2
Order By: Relevance
“…1,3,7,12,13 However, a previous study that classified non-HRS renal failure into 4 groups (mean glomerular filtration rate [GFR] in the 4 groups ranging from 47 to 140 mL/min) reported that there was no difference in patient survival between the different groups. 2 The discrepant results of this study, contrary to our findings, could be explained by the small sample size; more importantly, the patients were divided into 4 groups based on GFR obtained at the time of initial liver transplant evaluation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,3,7,12,13 However, a previous study that classified non-HRS renal failure into 4 groups (mean glomerular filtration rate [GFR] in the 4 groups ranging from 47 to 140 mL/min) reported that there was no difference in patient survival between the different groups. 2 The discrepant results of this study, contrary to our findings, could be explained by the small sample size; more importantly, the patients were divided into 4 groups based on GFR obtained at the time of initial liver transplant evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8] In addition, use of immunosuppressants such as cyclosporine and tacrolimus may cause further deterioration in renal function in this population. [7][8][9][10] Preoperative serum creatinine levels have been shown to be an important predictor of postoperative sepsis, 11,12 number of days spent in the intensive care unit, 3,13 need for preoperative and postoperative dialysis, 2,13 overall cost of liver transplantation, 13,14 and short-term graft and patient survival rates. 1,7,8,11,12,15 In one study, 2-year patient and graft survival rates were found to be similar in 31 patients with HRS and 263 without HRS.…”
mentioning
confidence: 99%
“…2,[8][9][10][11][12][13][14][15][16][17][18][19] Even mild elevations in serum creatinine level to greater than 1.0 to 1.6 mg/dL have predicted an increased incidence of post-OLT dialysis and death. 8,13,15,[19][20][21][22] Mortality is particularly common in patients with fulminant hepatic failure (FHF) and renal insufficiency. 21,23 Mortality seems to be explained by the serious medical condition of patients developing ARF, evidenced by their higher Acute Physiology and Chronic Health Evaluation II (APACHE II) scores (16 Ϯ 0.4 without ARF v 23.2 Ϯ 0.8 with ARF) and number of associated medical illnesses compared with those without renal failure.…”
Section: Pre-olt Renal Failurementioning
confidence: 99%
“…28,29 involves balancing the risk of procedure against the patient's probability of surviving without this treatment. While sevTo use a model derived from patients who did not receive transplants suggests a benefit from transplantation, must be eral factors, predictive of poor post-operative outcome, have been described, 25,26 predicting the prognosis of ALD in terms done with considerable caution. The group from which the model was derived and the patients who received transplants of survival without transplantation is a much more difficult problem.…”
mentioning
confidence: 99%